2022
DOI: 10.3390/genes13101884
|View full text |Cite
|
Sign up to set email alerts
|

Host Genetic Risk Factors Associated with COVID-19 Susceptibility and Severity in Vietnamese

Abstract: Since the emergence and rapid transmission of SARS-CoV-2, numerous scientific reports have searched for the association of host genetic variants with COVID-19, but the data are mostly acquired from Europe. In the current work, we explored the link between host genes (SARS-CoV-2 entry and immune system related to COVID-19 sensitivity/severity) and ABO blood types with COVID-19 from whole-exome data of 200 COVID-19 patients and 100 controls in Vietnam. The O blood type was found to be a protective factor that we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 44 publications
0
10
0
2
Order By: Relevance
“…Heterogeneous findings were observed regarding the correlation between genetic variations and COVID-19 susceptibility and severity [ 8 , 9 , 45 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Heterogeneous findings were observed regarding the correlation between genetic variations and COVID-19 susceptibility and severity [ 8 , 9 , 45 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…To be more precise, rs2531743 is located at 3p21.31, which has been previously linked to COVID-19 outcomes in eleven GWAS. SLC6A20 has been shown to interact with ACE2 in the membrane of small intestinal enterocytes, suggesting a relationship with COVID-19 illness [ 23 ]. Recent research has also demonstrated a link between SARS-CoV-2 sensitivity and SLC6A20 gene variants in Vietnamese [ 23 ] and Native American [ 33 ] populations.…”
Section: Discussionmentioning
confidence: 99%
“…SLC6A20 has been shown to interact with ACE2 in the membrane of small intestinal enterocytes, suggesting a relationship with COVID-19 illness [ 23 ]. Recent research has also demonstrated a link between SARS-CoV-2 sensitivity and SLC6A20 gene variants in Vietnamese [ 23 ] and Native American [ 33 ] populations. In addition, it was suggested that SLC6A20 is a novel regulator of glycine levels [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Major risk factors for severe disease complications (and death) include demographic characteristics (male sex and age above 65 years) and co-morbidities such as obesity 7,8 , hypertension, diabetes, chronic pulmonary, renal, respiratory or liver disease, immunode ciencies, cancer, and cardiovascular disease, but these factors do not fully explain the wide range of clinical severity 9,10 . A possible explanation for these ndings is that the host genetic variations affecting the structure or function of essential proteins play a critical role in the entry and spread of SARS-CoV-2 and determine the severity of COVID-19 course and outcome 11 .…”
Section: Introductionmentioning
confidence: 99%